α-methyltryptophan-mediated protection against diabetic nephropathy in db/db mice as studied with a metabolomics approach - Cai, Aimin; Shen, Dingchao; Xiong, Qiushuang; Ding, Jie; Ding, Yang; Lin, Xinlu; Chen, Lijia; Yao, Qing; Lin, Guangyong; Chen, Ruijie; Ganapathy, Vadivel; Kou, Longfa (Frontiers in Pharmacology, 2025)
IntroductionDiabetic nephropathy (DN), a major complication of diabetes, presents with poor clinical outcomes and affects patients throughout their lifetime. α-Methyltryptophan (α-MT) is a blocker of the amino acid transporter. SLC6A14 and also an inhibitor of indoleamine 2,3-dioxygenase-1 (IDO1).MethodsIn this study, we employed a nuclear magnetic resonance-based metabolomic approach to investigate the therapeutic effects of α-MT in a db/db mouse model of DN and explore the underlying molecular mechanisms.ResultsThe results of the study demonstrated that α-MT significantly reduced the urinary excretion of albumin and creatinine, improved kidney function, and decreased renal fibrosis in db/db mice. Metabolomic analyses of kidney tissues and urine samples indicated that db/db mice displayed increased activity of the enzyme IDO1, and alongside pronounced metabolic disturbances. These disturbances are chiefly characterized by alterations in amino acid metabolism, energy production pathways, membrane biochemical features, and nicotinamide metabolism, all of which have been implicated in mTOR signaling and apoptotic pathways.DiscussionAdministration of α-MT to db/db mice showed evidence of IDO1 inhibition and rectification of metabolic dysfunctions with concurrent suppression of mTOR signaling and apoptosis. These findings highlight the potential of α-MT as a promising therapeutic agent for diabetic nephropathy.